(untitled) (Advances in Applied Mathematics and Mechanics, 2025)
In this paper, a hybrid Immersed-Boundary/Body-Fitted-Grid method is extended to simulate the complex fluid-structure-interaction (FSI) problems involved in the flows through a bileaflet mechanical heart valve (BMHV). The background grid is discretized with a body-fitted gird while the freely-rotating leaflets are treated by an immersed boundary method named the local domain-free-discretization (DFD) method. For simulation of turbulence involved in BMHV flows, the wall-modelled large eddy simulation is implemented in the DFD framework. In order to address the instability issue associated with low-mass structures, the strong coupling (SC) strategy is employed. To accelerate the convergence of SC-FSI sub-iteration, we adopt the under-relaxion scheme with an optimal relaxion coefficient and Hamming’s 4th-order predictor-corrector scheme. To validate the SC schemes for low-mass structures, numerical experiments on the vortex induced vibration of an elastically mounted cylinder are carried out. Finally, the present method is applied to simulate and investigate the pulsatile flows through a BMHV at physiologic conditions, in which complex fluid-structure interactions are involved. The computed results agree well with the published numerical or experimental data.